2019
DOI: 10.1111/aman.13274
|View full text |Cite
|
Sign up to set email alerts
|

The Life of Winds: Knowing the Namibian Weather from Someplace and from Noplace

Abstract: This article brings the two questions, how and what we know, into a productive dialog to explain the difference between indigenous and scientific environmental knowledge. In the case I explore, scientists and Damara pastoralists ( ǂnūkhoen) both relate the arrival of the rains in arid Namibia to the interplay between two winds.However, when it comes to explaining those observations, their accounts could hardly be more different. While Indigenous people understand the arrival of the rains as a play between lovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 41 publications
0
45
0
Order By: Relevance
“…These observations link up with ontological debates in environmental anthropology (Burman 2017;Goldman, Daly, and Lovell 2016;Knox 2015;Mészáros 2020;Schnegg 2019;Whitaker 2019). In my previous work, I have also shown that Namibian scientists and Damara people share many observations about the winds, the rains, and climate change.…”
Section: Ontological Polyphonymentioning
confidence: 71%
See 2 more Smart Citations
“…These observations link up with ontological debates in environmental anthropology (Burman 2017;Goldman, Daly, and Lovell 2016;Knox 2015;Mészáros 2020;Schnegg 2019;Whitaker 2019). In my previous work, I have also shown that Namibian scientists and Damara people share many observations about the winds, the rains, and climate change.…”
Section: Ontological Polyphonymentioning
confidence: 71%
“…ǂNūkhoen people have a detailed understanding of how and why it rains (Schnegg 2019). This knowing makes two humanized winds, one female (huri ǂoab) and one male (tū ǂoab), responsible for the rain.…”
Section: Windsmentioning
confidence: 99%
See 1 more Smart Citation
“…They differ in other aspects though: Herero households are more entwined with the monetary economy and male household members especially are often experienced with labor migration, while Himba herders are subsistence oriented and have little experience with the labor market (see Bollig 2006; Tönsjost 2013; Van Wolputte 2007). Damara people speak an entirely different language, their kinship organization is rather distinct from the other two communities, and labor migration, remittances, and social transfers are as important as natural resource-based strategies like herding (Greiner 2008; Pauli 2009; Schnegg 2009, 2019).…”
Section: The Lings Projectmentioning
confidence: 99%
“…2 The approach we present in this article was developed in the Local Institutions in Globalized Societies (LINGS) project, which aimed to understand institutional solutions for managing water in arid Namibia (Schnegg 2016(Schnegg , 2018Schnegg and Linke 2015). At the ethnographic level, the historical dynamics of water management and the complex interweaving of power, kinship, and identity, as well as cultural norms and standards, were explored in ethnographic case studies of specific places (Linke 2017;Menestrey Schwieger 2015, 2017, 2019. On the basis of rich ethnographic data produced in a number of ethnographic field studies, several hypotheses about the distribution of institutional solutions and their connection with power distribution, wealth differentials, and embeddedness of a community in wider regional networks through labor, trade or educational measures, and the like were formulated.…”
mentioning
confidence: 99%